Evaluation of Second-Look Transurethral Resection in Re-Staging of Patients With Superficial Bladder Cancer - Zaman, Md Masud; Hasan, Md Sajid; Chowdhury, Golam Mowla; Rahman, Md Shafiqur; Rahman, AKM Mahbubur (Bangladesh Journal of Urology, 2020)
Objective: The Objective of this study was to evaluate the second-look transurethral resection (TUR) from the base of the previously resected bladder tumour in avoidance of staging errors, possibility of changing treatment strategy, and determination of risk factors of up-staging in patients with a diagnosis of superficial bladder cancer. Materials and Methods: In this cross sectional study, 50 cases of superficial bladder cancers (pTa and pT1) were included where muscle coat were absent in histopathologic report of first TURBT. A second-look TUR from the tumour site were done after 4 weeks following the initial resection. At the second-look TUR, resection from the base of the previously resected area was performed for restaging. Finally, histopathologic findings of the second TURBT were compared with those of the initial one by appropriate statistical analysis. Results: Out of 50 patients, 27 (54%) had residual malignant tissue in histopathological report of second-look TUR, while 23 (46%) were tumour free (no residual malignant tissue) at second-look TUR. In this study, total up-staging of tumour found in 18 (36%) patients. Out of them, 6 (12%) and 2(4%) patients were up-staged from pTa to pT1 and PT2 respectively. 10 (20%) were up-staged from PT1 to muscle-invasive (pT2). So, total percentage of staging errors (under staging) detected in second-look TUR was 36% cases. Appearance (sessile), size (>3 cm) and stage (pT1) of the tumour at the initial resection were independent risk factors for up-staging to muscle invasive disease detected at second-look TURBT. Conclusions: Second-look TURBT is a valuable procedure for detection of residual tumour and accurate staging of non-muscle invasive bladder tumour. It also changed the treatment strategy of a significant proportion of patients. It is useful for tumours at high risk of recurrence and progression such as large size, sessile, multiple and T1 high grade tumours, particularly when there is inadequate or no muscularis propria in the specimen. Bangladesh Journal of Urology, Vol. 18, No. 1, Jan 2015 p.16-22